The effects of post-test counselling on condom use among prostitutes in The Gambia. - Pickering, H; Quigley, M; Pépin, J; Todd, J; Wilkins, A (1993)
OBJECTIVES: To determine the effect of counselling on condom use by prostitutes. DESIGN: Cohort study. SETTING: Field-based study in The Gambia. PARTICIPANTS: Thirty-one (12 HIV-positive and 19 HIV-negative) prostitutes. INTERVENTIONS: Post-test HIV counselling. MAIN OUTCOME MEASURES: Levels of condom use. RESULTS: Overall, counselling had no effect on condom use. CONCLUSIONS: Scarce resources should be directed towards providing condoms in bars rather than counselling.